2005
DOI: 10.1080/00288233.2005.9513659
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maternal shearing and thyroid hormone treatments in mid pregnancy on the birth weight, follicle, and wool characteristics of lambs

Abstract: Mid pregnancy shearing of ewes has been associated with a short-to medium-term increase in maternal thyroid hormone concentrations. To determine the role of this elevation in the observed changes in lamb birth weight and fibre characteristics, ewes in mid pregnancy were either: shorn at day 70 of pregnancy with thyroid glands left intact (Shorn), unshorn with intact thyroid glands (Unshorn), thyroidectomised but left unshorn with a short-term elevation in thyroxine (T4) concentrations in mid pregnancy (Tx+T4),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Chronic cold stress resulting from a short fleece during winter was likely to have long term consequences on the ewe and the fetus. Thyroid hormone concentrations became elevated after mid-pregnancy shearing as a result of cold stress (Symonds et al, 1989), however, elevated thyroid hormones alone did not result in increased lamb birth weight (Kenyon et al, 2005). Therefore, the mechanism of mid-pregnancy shearing that produces the increase in lamb birth weight may be chronic stress.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Chronic cold stress resulting from a short fleece during winter was likely to have long term consequences on the ewe and the fetus. Thyroid hormone concentrations became elevated after mid-pregnancy shearing as a result of cold stress (Symonds et al, 1989), however, elevated thyroid hormones alone did not result in increased lamb birth weight (Kenyon et al, 2005). Therefore, the mechanism of mid-pregnancy shearing that produces the increase in lamb birth weight may be chronic stress.…”
Section: Discussionmentioning
confidence: 98%
“…The lamb birth weight increase caused by midpregnancy shearing was not due to an increase in ewe feed intake (Kenyon et al, 2002b;Revell et al, 2002), longer gestation length (Kenyon et al, 2002c), elevated maternal thyroid hormone concentrations (Kenyon et al, 2005) or events involved with being yarded (Corner et al, 2006). Stressors during pregnancy caused by transport (cattle) and isolation (sheep) have resulted in increased fetal (Lay et al, 1997) and birth weights (Roussel et al, 2004), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Such changes could potentially increase foetal thyroid hormone and effect follicle development at a critical time. Kenyon et al (2005) investigated this hypothesis through use of thyroidectomies and exogenous administration of triiodothyronine and thyroxine, but found that any effects on fibre attributes could not be solely attributed to elevated maternal thyroid hormones. Another study showed thyroxine definitely involved in the development of follicle morphology, but that any alterations which occurred from supplementation with thyroxine or inhibition of thyroxine (with propylthiouracil) did not alter subsequent fleece attributes (McDowall et al, 2011).…”
Section: Time Of Shearingmentioning
confidence: 99%
“…The increase in lamb birth weight observed is not due to increased gestation lengths (Kenyon et al, 2002c), increased ewe feed intakes (Kenyon et al, 2002b;Revell et al, 2002), changes in the ewe's metabolism (Kenyon et al, 2002b) or increased maternal thyroid hormone (T3 and T4) concentrations (Kenyon et al, 2005). Other stressors such as transport and isolation increase fetal weight in late gestation.…”
Section: Introductionmentioning
confidence: 99%